2015
DOI: 10.4137/vrt.s35331
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection and Clinical Implications of HTLV-1 Infections among Antiretroviral Therapy-Naïve HIV-1-Infected Individuals in Abuja, Nigeria

Abstract: BACKGROUNDIndividuals with human T-cell lymphotrophic virus type-1 (HTLV-1)/HIV-1 coinfection have been demonstrated to undergo CD4+ lymphocytosis even in the face of immunodeficiency and increased vulnerability to opportunistic pathogens that can lead to poor prognosis.OBJECTIVEThis study investigated the prevalence as well as the effects of HIV-1/HTLV-1 coinfection on CD4+ cell counts, routine hematology, and biochemical parameters of study participants.MATERIALS AND METHODSThis prospective cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 40 publications
1
23
2
Order By: Relevance
“…In our study, the highest prevalence of anti-HTLV-1/-2 IgG was highest among subjects within 15-24 years (20.0%) and least among those within 24-35 years (4.2%). This agreed with findings of Nasir et al [11] who reported the highest prevalence of HTLV-1 among the age group 21-30 years. This could be because this population age range represents the leading sexually active age group in Nigeria.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In our study, the highest prevalence of anti-HTLV-1/-2 IgG was highest among subjects within 15-24 years (20.0%) and least among those within 24-35 years (4.2%). This agreed with findings of Nasir et al [11] who reported the highest prevalence of HTLV-1 among the age group 21-30 years. This could be because this population age range represents the leading sexually active age group in Nigeria.…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence rate of 19.8% for recent HTLV-1/-2 infection in HIV/AIDS patient reported in this study was lower than 25.7% HTLV −1/-2 IgM seroprevalence reported by Adeoye et al [6]. However, IgM seroprevalence was significantly higher than 4.9% seroprevalence of HIV-1/HTLV co-infection in Abuja [11], and 1.8% HTLV/HIV-1 coinfection in KwaZulu-Natal by Rego et al [14] and 5.2% HTLV/ HIV coinfection prevalence in Guinea-Bissau [15]. The difference is most likely due to the difference in the laboratory protocol in detecting HTLV.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…The triad presentation of HTLV-1, ATLL and severe/refractory hypercalcaemia has been described in case reports [ 6 - 9 ]. However, the true prevalence of this presentation is unknown, largely due to misdiagnosis and underreporting as HTLV-1 is seldom considered for investigation in HIV infected individuals [ 10 ]. Current areas of uncertainty surrounding HTLV-1 co-infection include its impact on the progression of HIV disease and the initiation of antiretroviral therapy in countries where access to these drugs are restricted [ 3 , 11 ].…”
Section: Introductionmentioning
confidence: 99%